Thermoplastic material for immobilization purposes
By using specific compositions and processes in the thermoplastic material of the immobilization device, the problem that the material is difficult to balance between high flexural modulus and comfort is solved, and the high-performance immobilization effect of the material in the melting and cooling state is achieved.
Patent Information
- Application Number
- CN202380048942.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-02
- Publication Date
- 2025-02-07
AI Technical Summary
The thermoplastic materials of existing immobilization devices are difficult to take into account between high bending modulus and comfort, and the anisotropic mechanical properties of the material lead to the device being easily deformed during use, affecting the immobilization effect.
A composition is employed that contains 30% to 62% by weight of the first polymer (such as polycaprolactone), 15% to 35% by weight of spherical filler, 4% to 20% by weight of the thermoplastic elastomer and optionally Contains 2 to 20 wt% of the second polymer and 0 to 7 wt% of the total additive. The composition produces thermoplastic composites through an extrusion process, ensuring that the material has high drape in a molten state and sufficient stiffness after cooling.
The balance between high bending modulus and comfort of thermoplastic materials is achieved, providing good adaptability and stability, ensuring that the immobilization device is not easily deformed during use, and can effectively support and fix the body parts.
Smart Images

Figure BDA0005201274420000131 
Figure BDA0005201274420000142 
Figure HDA0005201274430000011
Abstract
Description
Technical Field
[0001] The present invention relates to a composition and a thermoplastic composite material for use in an immobilization device for immobilizing at least a portion of a human or animal body part. The present invention also relates to a method for making such a composite material and immobilization device. Background Art
[0002] The use of fixation and immobilization devices to immobilize a part of the body has become a well-known technique in applications such as orthopedics and prosthetics, physical rehabilitation, radiation oncology, and diagnostic imaging. These applications, particularly physical rehabilitation, require that the immobilization device can be molded directly on the patient at the activation temperature, exhibit good mechanical properties and surface finish, and be lightweight and comfortable for the patient. Important applications of immobilization devices include physical rehabilitation applications and orthopedic applications, such as in splints and braces to immobilize and protect inflamed or injured joints, support and immobilize ligaments and fractures, as well as muscle structures and foot ailments, such as in shoe insoles (shoe beds).
[0003] To produce immobilization or fixation devices suitable for the aforementioned applications, sheet-like thermoplastic materials are typically used. These materials are molded to conform as closely as possible to the body part to be immobilized. For years, research has continued to develop materials that meet the specific requirements of the envisioned application. The use of sheets of thermoplastic material that can be molded directly onto the body part to be immobilized has garnered significant attention because it allows for the highest degree of precision in immobilization. The size and shape of the immobilization device can be directly adjusted to suit the individual patient's location of the body part to be immobilized, and can be adjusted over time by remolding the immobilization device. To allow this direct molding, the thermoplastic material's melting temperature must be low enough to be tolerated by the body. Furthermore, the material must exhibit sufficient formability and elasticity in the molten state for a period long enough to allow molding, but not too long to save clinical time and minimize the risk of deformation after molding. Thermoplastic materials particularly suitable for direct molding onto body parts are often based on polycaprolactone. In practice, a polycaprolactone-based sheet is heated in a warm water bath for a sufficient time to achieve softening and melting of the material, and then the sheet is applied to the body part to be immobilized, shaped to conform to the body part, and allowed to cool.
[0004] For immobilization devices, not only good adaptability is important. Another important feature (particularly for applications where high rigidity is required, such as in antispasmodic braces, dorsal locking braces, and wrist cock-ups) is that the device has a high flexural modulus. The material should have a sufficiently high flexural modulus to minimize the risk of device deformation and the ability of body parts to move. The material should also provide high stability during use of the immobilization device, i.e., when immobilized by the immobilization device, restrict body parts from moving relative to the immobilization device. The higher the stability, the more difficult it is to move body parts under immobilization.
[0005] To achieve high-stiffness immobilization devices made of thermoplastic materials, attempts have been made to reinforce thermoplastics with short glass fibers, which offers the potential to achieve high flexural modulus levels, as described in WO 2020 / 006615 and US Pat. No. 5,584,800. However, the extrusion of glass-fiber-reinforced thermoplastics results in sheets with anisotropic mechanical properties. This phenomenon is due to the orientation of the glass fibers in the direction of extrusion flow. Consequently, the transverse tensile resistance differs significantly from the tensile resistance in the extrusion direction.
[0006] WO 2020 / 006615 also describes the use of talc as a filler in the composition in amounts of 5 to 60 wt%. Talc is known to be plate-like (and therefore not spherical) with an aspect ratio of 5:20 (see Handbook of fillers, edition 4, (2016), chapter 2, Fillers-origin, chemical composition, properties, and morphology, pages 218-221, by Wypych, George). The document further describes the use of silver nanoparticles in very low amounts (0.05 wt% or less) to act as fungal and bacterial growth inhibitors.
[0007] To avoid the aforementioned issues of anisotropic mechanical properties, other attempts have involved producing reinforced thermoplastic sheets by injection molding rather than extrusion, where the glass fiber orientation is minimal, resulting in a more isotropic product. However, production by extrusion is preferred over injection molding because it is a continuous process, more cost-effective, and produces higher volumes.
[0008] Therefore, there is a need for a thermoplastic material for an immobilization device that provides high modulus, such as flexural modulus, comfort, and good adaptability. In addition, such an immobilization device should provide good patient comfort and should not be made of materials that cause allergic reactions, irritation reactions, and / or sensitization reactions. Further preferably, the thermoplastic material can be produced by extrusion to produce sheets, preferably flat sheets. The thermoplastic sheet should be easy to pre-cut into different patterns before being formed into a three-dimensional object by simple heating at relatively low temperatures. The immobilization device should be able to withstand repeated bending constraints to ensure that the body part is supported during the wear of the immobilization device.
[0009] A new composition has been discovered that can be used to produce thermoplastic sheets having high stiffness without compromising other properties such as ease of molding or forming, drape, conformability, and ease of edge finishing. Summary of the Invention
[0010] Therefore, the present invention provides a composition comprising, based on the total weight of the composition:
[0011] a. 30 wt% to 62 wt% of a first polymer having a melting temperature below 100°C, preferably 40°C to 75°C;
[0012] b. 15 wt% to 35 wt% of a spherical filler and optionally up to 15 wt% of another type of filler;
[0013] c. 4 wt% to 20 wt% of a thermoplastic elastomer;
[0014] d. Optionally, 2 wt% to 20 wt% of a second polymer, the second polymer having a higher flexural modulus than the first polymer;
[0015] e. 0 wt% to 7 wt% of total additives.
[0016] By carefully selecting its components and their amounts, the compositions according to the invention allow the production, particularly by extrusion, of thermoplastic composite materials suitable as immobilization devices that can be easily molded or formed around body parts. The product in the molten state exhibits highly drapeable behavior (it's soft, so it flows easily and conforms perfectly to the shape of the body part), yet becomes sufficiently rigid once it cools to room temperature. Despite their relatively high stiffness / hardness, orthoses and splints made from them are very comfortable. Furthermore, they are able to withstand repeated bending constraints, ensuring that the body part is effectively and sustainably supported / immobilized by the thermoplastic composite material.
[0017] The composition according to the invention is adjusted in such a way that the material does not cool or solidify rapidly and remains elastic and moldable, thereby providing the therapist with sufficient time to reshape and finish the orthosis.
[0018] For purposes of clarity and conciseness, features are described herein as part of the same or separate embodiment; however, it should be understood that the scope of the invention may include embodiments having a combination of all or some of the described features.
[0019] As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well. The term "or" includes any and all combinations of one or more of the associated listed items, unless the context clearly indicates otherwise (e.g., if an "either . . . or" structure is used). It should be understood that the terms "comprises" and "comprising" specify the presence of the stated features, but do not preclude the presence or addition of one or more other features. It should also be understood that when a particular step of a method is referred to as a subsequent step to another step, unless otherwise specified, it may directly follow the other step, or one or more intermediate steps may be performed before performing the particular step.
[0020] As used herein, the term "wt%" or "weight percent" or "percent by weight" refers to the mass fraction of a substance in a mixture divided by the total mass of the mixture, expressed as a percentage from 0 to 100.
[0021] As used herein, the term "thermoplastic composite" refers to a material composed of two or more connected materials and containing a matrix made of a thermoplastic polymer. Typically, a thermoplastic composite has different material properties than its individual components.
[0022] As used herein, the term "drapability" refers to the ability of a material to bend and conform to the surface of a curved article once it has been activated (i.e., heated to a target temperature, such as 65°C). The ability of a material to drape over an adherend surface can be characterized by its bend radius (i.e., the minimum radius to which the material can be bent without kinking, folding, or cracking). Alternatively, the drapeability of a material can be characterized by measuring the distance between the two edges of the material when bent over a curved article (e.g., a metal pin).
[0023] As used herein, the term "fatigue resistance" refers to the ability of a material to withstand multiple cycles of repeated bending until the sample breaks. A suitable and preferred evaluation method consists of the following steps: (A) cutting a sample of standard size (18 cm x 5 cm) from a thermoplastic sheet; (b) clamping half of the sample between two metal plates (1 and 2) at the bottom of a fatigue test bench (bench); Figure 1); (c) bending the top of the thermoplastic by 90° using the movable clamp 3; (d) straightening the thermoplastic by returning the movable clamp 3 to its initial position; and (e) counting the number of cycles (repeated bending and straightening) until the sample breaks into two parts.
[0024] The present invention provides a composition comprising at least a first polymer, a spherical filler, a thermoplastic elastomer and optionally a second polymer. The composition may further comprise additives.
[0025] The first polymer included in the composition according to the present invention is a thermoplastic polymer with a low melting temperature (typically below 100°C or even below 75°C). The melting temperature of the first polymer can be measured by differential scanning calorimetry (DSC). At a heating rate of 10°C / min, the measured melting point corresponds to the peak observed in the DSC heating curve. A first heating scan is typically performed to erase the sample's previous thermal history. After cooling to -80°C at a ramp of 10°C / min, a second heating scan is also performed at the same rate (10°C / min). Depending on the sample's thermal history, the melting temperature measured during the first heating may differ by several degrees from the melting temperature measured during the second heating scan. The intrinsic melting temperature (second heating peak) is the value corresponding to the melting temperature mentioned in this specification. Preferably, the melting temperature of the first polymer measured by DSC is between 40°C and 75°C, more preferably between 50°C and 70°C, and most preferably between 51°C and 61°C, as these temperatures can be supported by the human and animal body and allow for direct molding onto the body.
[0026] The example of thermoplastic polymer with this melting temperature is thermoplastic polyurethane, thermoplastic polyester and thermoplastic polyolefin.Can use only one of described polymer or two or more blends thereof.The example of suitable thermoplastic polyolefin includes ethylene copolymer, ethylene-vinyl acetate copolymer, propylene copolymer, ethylene-propylene copolymer or polycis-isoprene.The example of suitable thermoplastic polyester includes polycaprolactone, polymer fatty acid ester, butylene adipate-terephthalate copolymer, succinate-butylene adipate copolymer.Preferred first polymer is selected from the group consisting of: polycaprolactone (PCL), thermoplastic polyurethane (TPU), ring-opening polycycloolefin and polycis-isoprene.Preferably, the first polymer according to the composition of the present invention is polycaprolactone (PCL) polymer, most preferably ε-polycaprolactone. ε-polycaprolactone is particularly preferred because it has a low melting point, below 75°C and particularly between 40°C and 70°C (as measured by DSC), exhibits good molding properties, and has a sufficiently long working time before solidification to allow direct molding onto the body. If desired, ε-polycaprolactone can be used in admixture with another thermoplastic, such as thermoplastic polyurethane.
[0027] Particularly preferred are first polymers (particularly ε-polycaprolactone) having a number average molecular weight Mn of at least 10.000 g / mol, more preferably at least 20.000 g / mol, most preferably at least 40.000 g / mol, in particular at least 50.000 g / mol. The number average molecular weight Mn of the first polymer of the present invention is generally at most 100.000 g / mol, preferably at most 90.000 g / mol. First polymers with a molecular weight above 100.000 g / mol may result in slower crystallization rates and reduce the moldability of the thermoplastic material in the molten state, thereby impairing the ability of the material to be shaped in the molten state and adversely affecting patient comfort. However, crystallization can be accelerated by adding nucleating agents. PCL with different molecular weights is commercially available from the company Ingevity under the trade name CAPA.
[0028] The composition according to the invention comprises 30 to 62 wt %, preferably 40 to 55 wt % of the first polymer. In particular, good results are obtained using PCL (i.e. polycaprolactone CAPA 6500, having a molecular weight of 50,000 g / mol and a flexural modulus of 411 MPa according to ASTM D790).
[0029] For example, the molecular weight Mn of a compound can be determined by gel permeation chromatography (GPC) using THF as eluent according to DIN 55672-1. Unless otherwise stated, the molecular weights listed are those determined by GPC.
[0030] Suitable fillers for the present invention include inorganic or organic materials that are insoluble in polymers when the polymer is in the molten phase and have a spherical morphology, such as spheres and bubbles. Spherical fillers preferably have a shape factor lower than 3, preferably lower than 2, most preferably lower than 1.5, wherein the term "shape factor" refers to the ratio between the size of the maximum dimension axis of the filler particles and the size of the minimum dimension axis of the filler particles. The shape factor is generally 1 to 3, preferably 1 to 2, more preferably 1 to 1.5, and most preferably about 1. This type of filler provides isotropic performance in extrusion processing. In addition, using spherical fillers can obtain more stable flow in the extrusion process, thereby making the production process easier.
[0031] Therefore, fillers having an elongated shape (such as needles or plates), especially fillers having a shape factor of at least 5, such as talc, mica, kaolin (whose shape factor is generally 10-100), are not included in the term "spherical fillers".
[0032] Spherical fillers can also be defined by the material's hardness, such as on the Mohs hardness scale. The Mohs hardness scale defines the scratch resistance of various materials by the ability of a harder material to scratch a softer material. In preferred embodiments, the Mohs hardness scale is greater than 1.5. More preferably, the Mohs hardness is greater than 2, and most preferably, greater than 5.
[0033] Although the spherical fillers used in the present invention can have solid, porous or hollow structures, solid structures are preferred, such as solid glass spheres, because of the fact that their shape is retained in the thermoplastic composite, while shell-type spherical fillers (such as hollow bubbles) may break or deform during the manufacturing process of the composite, especially during the extrusion process.
[0034] Preferably, the spherical filler has a diameter size of less than 120 μm, preferably less than 100 μm, more preferably 40 μm to 80 μm. Larger sizes generally result in higher pressures during extrusion, especially when fine screens are used to eliminate potential dirt and impurities.
[0035] Preferred spherical fillers for use according to the present invention are glass balloons or glass beads.
[0036] The composition according to the invention comprises 15-35 wt %, preferably 22-32 wt %, more preferably 22-30 wt % of spherical fillers. Above 35 wt %, brittle behavior of the thermoplastic composite is observed: a flat sheet of the thermoplastic composite breaks upon bending at only 90°. This weak performance is due to filler agglomeration and the absence of chemical bonding between matrix and filler. Below 15 wt %, sufficient strength and stiffness are generally not achieved. In particular, good results can be achieved using glass beads with a diameter of 2.8 μm to 100 μm, such as Spheriglass 2530 from Potters Industries.
[0037] In some embodiments, the composition according to the present invention may contain, in addition to the spherical filler, another type of filler (which may therefore be elongated), such as nanoclay, talc, mica, kaolin, silica, calcium carbonate. This optional additional filler may be present in an amount of less than 15 wt %, preferably less than 12 wt %, more preferably less than 10 wt %, and most preferably less than 5 wt % of the total composition. The total amount of fillers (spherical and other types) is preferably from 21 wt % to 43 wt %, more preferably from 25 wt % to 35 wt %.
[0038] The thermoplastic elastomer (TPE) comprised in the composition according to the present invention may be any polymer that exhibits elastic, flexible or rubbery properties at room temperature and can be processed using plastic manufacturing techniques such as extrusion, injection molding and blow molding.
[0039] The thermoplastic elastomer is preferably a binary mixture of soft segments and hard segments, wherein the soft segments are rubbery in that their glass transition temperature is below room temperature.
[0040] In one embodiment, the hard segment of the TPE is an amorphous homopolymer having a glass transition temperature above room temperature. In another embodiment, the hard segment of the TPE is a semi-crystalline polymer.
[0041] The thermoplastic elastomer preferably has a Shore A hardness of up to 92, preferably 30 to 80, and is preferably compatible with the first polymer (e.g. PCL). Suitable thermoplastic elastomers for use according to the present invention include thermoplastic olefin elastomers (TPO), thermoplastic polyurethane elastomers (TPU) and so-called thermoplastic styrene elastomers (TPS), such as polystyrene-butadiene or polystyrene-isoprene copolymers, typically with a styrene content of up to 60 wt%, preferably 15 wt% to 50 wt%, more preferably 30 wt% to 35 wt%, wherein the styrene phase is partially miscible with the PCL and the rubber phase (butadiene or isoprene) improves toughness (comfort).
[0042] The molecular weight of the thermoplastic elastomer is preferably higher than 100,000 g / mol, preferably higher than 150,000 g / mol, more preferably about 170,000 g / mol. The viscosity of such thermoplastic elastomers, expressed as melt flow rate (200° C., 5 kg) measured according to standard ISO 1133, is preferably higher than 1 g / 10 min, preferably higher than 5 g / 10 min, more preferably higher than 10 g / 10 min, although higher viscosity thermoplastic elastomers with a melt flow rate (MFR) lower than 1 g / 10 min may also be used. Melt flow rate is a measure of the ease with which a thermoplastic polymer melt flows. It is defined as the mass (in grams) of polymer that flows through a capillary of a specific diameter and length within 10 minutes under a pressure applied by a specified optional weight for an optional specified temperature. The melt flow rate is inversely proportional to the viscosity of the melt under the test conditions. In some embodiments, the thermoplastic elastomer may contain a viscosity reducer, such as mineral oil. The melt flow rate (200° C., 5 kg) of this component may be in the range of 20 g / 10 min to 40 g / 10 min.
[0043] The composition according to the present invention comprises 4 wt % to 20 wt %, preferably 6 wt % to 15 wt %, most preferably 6 wt % to 10 wt % of such thermoplastic elastomer. Lower amounts of thermoplastic elastomer result in high stretchability and low stability of the material during heating and shaping of the composite material on the patient. Higher amounts of thermoplastic elastomer result in composite materials that are difficult to shape at melting temperatures (typically 65° C.) because the composite material is too hard at the activation temperature and too soft at room temperature (during use). If a low viscosity thermoplastic elastomer as specified above is used, the amount used can be as high as 15 wt %. For higher viscosity thermoplastic elastomers (such as those with an MFR of less than 1 g / 10 min), lower amounts (up to 10 wt %) must generally be used.
[0044] In particular, good results have been obtained with polystyrene-butadiene polymers, namely Kraton D1101AS or Kraton D4153 ES (with mineral oil to reduce viscosity).
[0045] Optionally, a second polymer is included in the composition according to the present invention. The second polymer is a polymer with a higher flexural modulus than the first polymer, typically a so-called reinforced thermoplastic, which may optionally include a filler to affect the flexural properties of the reinforced thermoplastic. If the filler is included in the second polymer, for the purposes of the present invention, it is considered as part of the second polymer d), and it is not calculated with the amount of the filler in b). Therefore, in the case where the first polymer is PCL, the second polymer should preferably have a flexural modulus of at least 800 MPa (measured according to standard ASTM D790). Examples of polymers with such a flexural modulus can be selected from polyester, polyolefin or polyamide families. The preferred second polymer included in the composition according to the present invention is a polyolefin, such as polypropylene (PP), or a composition based on polypropylene. This second polymer provides physical retention, which makes the resulting product easy to deform and shape without being too fluid.
[0046] If this second polymer is present in the composition according to the invention, its amount is generally in the range of 1 to 20 wt%, preferably 5 to 15 wt%. Below 5 wt%, if the thermoplastic elastomer is present in limited amounts, the flexural modulus will not be high enough and shape retention will not be achieved. Above 20 wt%, it will be impossible to stretch and shape the composite material upon heating at 65°C, as the second polymer neither melts nor flows at this temperature.
[0047] The additives optionally included in the composition according to the invention may be any of the standard additives, such as pigments, antioxidants, thickeners, processing aids, stabilizers, plasticizers, lubricants, antistatic agents, nucleating agents, flow improvers.
[0048] The composition according to the present invention comprises 0 to 7 wt% of total additives, preferably 4 to 7 wt%, and most preferably 5.5 to 6 wt%. Preferably, a masterbatch of all additives can be prepared and added to the other ingredients of the composition. The amount of each individual additive present in the composition is preferably 0.1 to 4 wt%, more preferably 0.5 to 2%.
[0049] The composition according to the invention may contain 0.1 wt % to 0.5 wt %, preferably 0.3 wt % of a nucleating agent. The composition according to the invention may contain 2.5 wt % to 10 wt % of a wax. The composition according to the invention may contain 2 wt % to 8 wt %, preferably 4 wt % of an anti-sticking agent. The composition according to the invention may contain 0.5 wt % to 2.5 wt %, preferably 1.5 wt % of a pigment. The composition according to the invention may contain 0.05 wt % to 1 wt %, preferably 0.25 wt % of a lubricant. The composition according to the invention may contain 0 wt % to 0.5 wt %, preferably 0.05 wt % of an antioxidant.
[0050] The present invention also relates to a thermoplastic composite material produced from the composition according to the invention. Said thermoplastic composite material can be formed into a sheet which is suitable for use in an immobilization device.
[0051] In order to produce the thermoplastic composite material according to the present invention, each technology that those skilled in the art find suitable, such as extrusion or injection molding, can be used. Preferably, the thermoplastic composite material is manufactured by extrusion, including single-screw and twin-screw extrusion and processes based on extrusion, and can be in the form of particles, sheets and filaments, depending on the way of making customized products. Plastic extrusion is a well-known manufacturing process in which the raw plastic is melted and formed into a continuous profile, such as a film or sheet. The process starts by feeding the plastic material into the barrel of an extruder. The material is gradually melted by rotating the screw and by the mechanical energy generated by a heater arranged along the barrel. The molten polymer is then pressed into a mold, which shapes the polymer into a shape that hardens during the cooling process.
[0052] The production of the thermoplastic composite material of the present invention by extrusion is preferably carried out at a temperature range of 180°C to 200°C. Typically, all ingredients of the composition, except the spherical filler, are fed into the first open zone of the extruder barrel and mixed by the twin screws. The spherical filler is preferably fed into the extruder barrel later, when the composition has melted, via a side feeder. However, it is also conceivable to feed all ingredients into the first zone.
[0053] Another advantage of the present invention is that the end-use properties of the thermoplastic composite are set during the extrusion process and do not require any post-processing steps in the solid state. Such post-processing steps are vulcanization or cross-linking achieved by exposing the polymer composition to an external energy source (e.g., by heating, photon or electron beam irradiation), in the presence of a chemical cross-linking agent, which results in the formation of covalent bonds within, between, and through the various polymer chains of the composition.
[0054] Preferably, the thermoplastic material is produced in the form of a sheet. The thickness of the sheet can vary within a wide limit. When the thermoplastic composite material is used for an immobilization device for immobilizing a body part, the thickness typically varies between 1 mm and 4 mm, preferably 2.4 mm and 3.2 mm. Typically, a thickness of about 3.2 mm is used. Those skilled in the art will ensure that when selecting a suitable thickness, the thickness is large enough to meet the requirements of the intended application. For the immobilization device, the thickness is typically selected so that the flexural modulus and strength are ultimately within the limits required for the application, and the cooling time of the composite material after being heated to its melting or softening temperature is long enough to allow shaping around / around the body part to be immobilized.
[0055] The thermoplastic sheet of the present invention may be perforated or non-perforated. Methods of applying such perforations to thermoplastic sheets for use in immobilization devices are well known to those skilled in the art. Typically, to optimize the time available for template molding, the degree of perforation of the thermoplastic sheet will vary between 1% and 25%, where % refers to the percentage of the thermoplastic sheet surface that is perforated relative to the total surface area of the thermoplastic sheet.
[0056] According to the present invention, sheet-like thermoplastic composite materials are used to produce immobilization devices for immobilizing body parts. The materials of the present invention are particularly useful in the field of physical rehabilitation immobilization, such as orthoses and splints. Physical therapists, occupational therapists, hand therapists and orthotists soften the thermoplastic material in hot water or by hot air (dry heat) and then mold it directly onto the patient's affected body part to produce a shape that closely matches the anatomical contours of the patient's affected body part. Orthoses or splints are used to immobilize body parts to allow proper healing, prevent certain undesirable movements, or promote certain desired movements.
[0057] The thermoplastic composite material according to the present invention has high stiffness at room temperature. Therefore, it is particularly suitable for physical rehabilitation applications requiring high stiffness, such as anti-spasticity orthoses, dorsal locking orthoses, wrist lifts, short splints, or finger-based finger extension orthosis positions (after Dupuytren's release and splint rest). Despite the relatively high stiffness of the thermoplastic composite material, orthoses and splints made from it are very comfortable.
[0058] At elevated temperatures, such as about 65° C., the thermoplastic composite material according to the present invention is in a molten state, providing high drapability. In this molten state, the material is easily shaped or molded around the body part, thereby forming a good fit around the body part.
[0059] The thermoplastic composite material according to the present invention generally has a drape of less than 5 cm, preferably less than 4 cm. Preferably, the drape is at least 0.5 cm, preferably at least 1 cm. In order to evaluate the drape, the test sample is cut into sheets with a size of 10 cm x 2.5 cm. A line is drawn in the middle of the test sample at 5 cm from the side. Thereafter, the test sample is heated in a water bath at the activation temperature and time (in most cases at 65°C for 3 minutes). After heating, the test sample is placed on a metal pin. Make sure the test piece is not touching anything and is positioned accurately in the center. The marked line should correspond to the metal pin. After this, release the test piece. As the test piece cools but is still warm, it will bend due to gravity. Once the sample has completely cooled, measure the distance (cm) between the two "legs" of the sample (as an indication of drape).
[0060] The thermoplastic composite material according to the present invention generally has a stress resistance (RTS) of less than 35 cm, preferably in the range of 15.5 cm to 35 cm, and more preferably in the range of 15.5 cm to 24 cm. RTS is a method for evaluating the stretch resistance of a sheet after activation (i.e., heating at 65°C for 3 minutes) by: (a) cutting a sample of standard size from an extruded sheet, (b) heating the sample in hot water (65°C) for 3 minutes, (c) removing the sample from the hot water, fixing one end of the sample with a clamp, and providing a standard weight (135 g) to the other end, (d) stretching the molten sample under gravity and cooling to room temperature, (e) the length (cm) of the stretched sample is the RTS value (cm), and (f) the shorter the stretched sample, the higher the stretch resistance.
[0061] The thermoplastic composite material according to the present invention typically has a fatigue resistance higher than 1000 cycles, preferably higher than 2000 cycles, more preferably higher than 2500 cycles, and most preferably higher than 3000 cycles or even higher than 4000 cycles.
[0062] Preferably, the thermoplastic composite material according to the present invention has a flexural modulus at least equal to or greater than that of the first polymer. Thus, when the first polymer is polycaprolactone, the flexural modulus is preferably at least 400 MPa, more preferably at least 500 MPa. Flexural modulus and maximum load are measured according to ASTM D790.
[0063] The specific ratios of the different compounds in the thermoplastic composite material according to the present invention provide some physical retention, so that in the molten state, the material does not flow completely, but can still be easily deformed, shaped, and reshaped to facilitate final corrections or necessary modifications during the patient's treatment. At room temperature, the material possesses sufficient strength to ensure good immobilization of the body part. Therefore, the thermoplastic composite sheet according to the present invention is particularly suitable for use in immobilization devices such as splints or orthoses.
[0064] For patient comfort, it is important that the material is activated / heated or molded at a temperature below 90° C., preferably below 80° C., more preferably below 75° C., and most preferably between 65° C. and 70° C. Typically, the material is activated at 65° C. but allowed to cool to 45° C. and 50° C. before being formed on the patient.
[0065] The thermoplastic composite material according to the present invention does not cool rapidly after heating, which provides the therapist with sufficient time to reshape and refine the orthosis. In particular, the inventors have observed that the time period available for molding the thermoplastic material can be at least 1 minute, particularly at least 1.5 minutes or at least 2 minutes, and sometimes exceeding 2.5 minutes. Typically, the available molding time is no longer than 15 minutes, preferably no longer than 12.5 minutes, particularly no longer than 10 minutes or at most 5 minutes, as this can reduce patient comfort due to increased cooling and waiting time.
[0066] The thermoplastic composite material according to the present invention can be coated with a thin layer of coating, such as a non-stick coating. Such coatings offer a good balance of residual tack, as they provide a slightly tacky surface, which is important for keeping the material in place during orthosis manufacturing so it doesn't move around, while also preventing it from sticking to the patient's skin. Suitable non-stick coatings are, for example, two-component acrylic-based coatings.
[0067] Another feature of the thermoplastic composite material according to the present invention is that it has sufficient residual tack to facilitate finishing the edges of a device used for immobilization. Due to the residual tack, the edges can be easily rolled down and adhered well. Furthermore, the edges are easily trimmed. DETAILED DESCRIPTION
[0068] The present invention is illustrated by, but not limited to, the following examples.
[0069] Example 1 (comparison example with other types of fillers):
[0070] Thermoplastic sheets having a thickness of 3.2 mm were produced by extrusion and had the composition shown in Table 1 below.
[0071] Two gravimetric feeders were used to feed the ingredients into Zone 1 of a ZSK twin-screw extruder (Coperion). The extrusion temperature was set at 150-160°C. The screw speed was set at 200 rpm. In samples 3, 4, and 5, the filler was fed into the extruder barrel via a separate feeder. In all other samples, all ingredients were fed into Zone 1 at once. The samples were extruded on a Tyson extruder (production grade) using only a flat die with a width of 120-150 cm.
[0072] The following properties were measured on the obtained sheets: RTS, drapability, maximum load and flexural modulus (all performed according to the above methods). The results are shown in Table 1.
[0073] From Table 1, it can be concluded that the use of fillers other than the spherical fillers according to the present invention does not provide satisfactory performance in terms of drapability and / or stiffness of the thermoplastic sheet obtained. In addition, the properties of the samples containing short glass fibers (Samples 4 and 5) differ significantly depending on the direction in which the properties are measured (extrusion direction or transverse direction).
[0074] Example 2:
[0075] According to the same method as in Example 1, a thermoplastic sheet having a thickness of 3.2 mm was produced by extrusion, which contained the ingredients shown in Table 2 below. In Sample 9, the filler was fed into the extruder barrel by a separate feeder. In all other samples, all ingredients were fed into the first zone at once.
[0076] The following properties were measured on the obtained sheets: RTS, drape, fatigue resistance, maximum load and flexural modulus (all performed according to the above methods). The results are shown in Table 2.
[0077] From Table 2, it can be concluded that the compositions according to the invention containing spherical fillers provide thermoplastic sheets with satisfactory properties in terms of stiffness, drapability, and remain elastomeric for a sufficiently long period of time in the heated state (Samples 7-9). In addition, the properties were measured in both directions (extrusion direction and transverse direction) and were found to be similar, which is advantageous compared to short glass fibers.
[0078] In Samples 10 and 11, talc was used instead of the spherical filler according to the present invention. This comparative example demonstrates that non-spherical fillers such as talc, which are frequently used as fillers in the prior art, do not provide the desired drape properties, making it more difficult to conform to the complex geometries of the human anatomy. Furthermore, experiments showed that Samples 7 and 8 outperformed Samples 10 and 11 in fatigue resistance, demonstrating a significant advantage over more commonly used fillers such as talc. This higher fatigue resistance allows the sheet to be bent more frequently during use.
[0079] Table 1
[0080]
[0081]
[0082] (*) Performance measured in the transverse direction (**) Performance measured in the extrusion direction
[0083] Table 2
[0084]
Claims
1. A composition, based on the total weight of the composition, comprising: a. 30 wt% to 62 wt% of a first polymer, the first polymer having a melting temperature below 100°C, preferably 40°C to 75°C; b. 15 wt% to 35 wt% of a spherical filler and optionally up to 15 wt% of another type of filler; c. 4wt% to 20wt% of a thermoplastic elastomer; d. Optionally, 2 wt% to 20 wt% of a second polymer, the second polymer having a higher flexural modulus than the first polymer; e. 0 wt% to 7 wt% of total additives.
2. The composition of claim 1, wherein the first polymer is a polycaprolactone (PCL) polymer.
3. A composition according to claim 1 or claim 2, wherein the spherical filler has a shape factor of 1 to 3. The composition according to claim 3 , wherein the spherical filler has a shape factor of 1 to 1.
5.
5. A composition according to any one of the preceding claims, wherein the spherical filler is not talc.
6. A composition according to any one of the preceding claims, wherein the spherical filler is a solid.
7. A composition according to any one of the preceding claims, wherein the spherical filler comprises solid glass spheres and the optional other type of filler comprises nanoclay.
8. The composition according to any one of the preceding claims, wherein the thermoplastic elastomer has a molecular weight higher than 100000 g / mol.
9. The composition according to any one of the preceding claims, wherein the thermoplastic elastomer is selected from the group consisting of a thermoplastic styrene elastomer or a thermoplastic polyurethane, the thermoplastic styrene elastomer preferably having a styrene content of 15 to 50 wt%, preferably the thermoplastic elastomer is a polystyrene-butadiene polymer.
10. The composition of any preceding claim, wherein the second polymer has a flexural modulus of at least 800 MPa.
11. A composition according to any one of the preceding claims, wherein the second polymer is selected from the polyester, polyolefin or polyamide family, preferably the second polymer is polypropylene, the second polymer preferably comprising a filler.
12. The composition according to any one of the preceding claims, wherein one or more additives are selected from the group consisting of pigments, antioxidants, thickeners, processing aids and slip agents.
13. A thermoplastic composite material made from the composition defined in any one of claims 1 to 12.
14. Thermoplastic composite material according to claim 13, which is made by extrusion, wherein all ingredients of the composition except the spherical filler are preferably fed in a first stage, and the spherical filler is subsequently added through a separate inlet.
15. The thermoplastic composite material according to any one of claims 13 to 14, having a drape of 0.5 cm to 5 cm, a stress resistance of 15.5 cm to 35 cm and a flexural modulus of at least 400 MPa.
16. The thermoplastic composite material according to any one of claims 13 to 15, in the form of a sheet, preferably having a thickness in the range of 1 mm to 4 mm.
17. Use of a thermoplastic composite material as defined in any one of claims 13 to 16 for the manufacture of an immobilization device for immobilizing at least a portion of a body part.
18. An immobilization device for immobilizing at least a portion of a body part, wherein said immobilization means comprises a sheet of thermoplastic composite material as defined in claim 16, wherein said sheet of thermoplastic composite material is shaped to conform to said body part to be immobilized.
Citation Information
Patent Citations
Method of enclosing a body member using an apertured, extruded sheet
US5584800A
Method for producing a polymer composite for use in orthopaedic devices and products thus produced
WO2020006615A1